Characterization Studies and Antimicrobial Efficacy of Silver Nanoparticles Synthesized Using Aspergillus niger: A Biological Driven Approach - B, Kiran Sharma; Dakshinamoorthi, Balakumaran Manickam; S, Jagadeeswari (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
For years, nanoparticles have been the subject of extensive research, continuously captivating researchers due to their minute size and distinctive surface properties. Among these, silver nanoparticles (AgNPs) stand out as particularly noteworthy, acclaimed for their remarkable biological, chemical, electrical, optical, and thermal characteristics. Moreover, the advent of biological synthesis methods has provided an environmentally friendly and cost-effective means of producing nanoparticles. In this study, the synthesis of silver nanoparticles (AgNPs) utilizing fungal isolates from marine soil samples was explored. A visible shift in color, from light to dark brown, signified the formation of silver nanoparticles through fungal mediation. Confirmation of the reduction reaction of silver ions in the fungal cell-free filtrates was achieved using UV-visible spectroscopy, which revealed a surface plasmon resonance peak at 420 nm. Scanning electron microscopy (SEM) affirmed the presence of spherical nanoparticles within the size range of 10-30 nm, while X-ray diffraction studies (XRD) validated the presence of metallic silver. The synthesized nanoparticles exhibited potent antimicrobial activity against both gram-positive and gram-negative clinical isolates, with minimum inhibitory concentration (MIC) values indicating their efficacy. This underscores the potential of these silver nanoparticles in combating major infections. Further assessment of this property was conducted through time-kill assays, revealing bacterial cell viability at various time intervals. The identification of fungi at the molecular level was accomplished through 16S rRNA sequencing.